2022
DOI: 10.1186/s40813-022-00287-6
|View full text |Cite|
|
Sign up to set email alerts
|

Farm management practices, biosecurity and influenza a virus detection in swine farms: a comprehensive study in Colombia

Abstract: Biosecurity protocols (BP) and good management practices are key to reduce the risk of introduction and transmission of infectious diseases into the pig farms. In this observational cross-sectional study, survey data were collected from 176 pig farms with inventories over 100 sows in Colombia. We analyzed a complex survey dataset to explore the structure and identify clustering patterns using Multiple Correspondence Analysis (MCA) of swine farms in Colombia, and estimated its association with Influenza A virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…As the swine population grows to meet rising demand, there is a greater likelihood of disease transmission among pigs. Several studies have shown that higher densities of pig farms and increased animal movement and transportation within different regions of the country, from and between swine farms, slaughterhouses, and markets, may facilitate the spread of SIV [ 21 , 42 , 44 ]. Moreover, these increased interactions between humans and pigs can lead to zoonotic or reverse zoonotic transmission of IAVs as demonstrated in other countries [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the swine population grows to meet rising demand, there is a greater likelihood of disease transmission among pigs. Several studies have shown that higher densities of pig farms and increased animal movement and transportation within different regions of the country, from and between swine farms, slaughterhouses, and markets, may facilitate the spread of SIV [ 21 , 42 , 44 ]. Moreover, these increased interactions between humans and pigs can lead to zoonotic or reverse zoonotic transmission of IAVs as demonstrated in other countries [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory disease management represents one of the most challenging problems in the swine industry, because of the multifactorial etiology associated with respiratory diseases such as housing conditions on the farm, population density, and biosecurity (Ciuoderis-Aponte et al, 2022). Therefore, it is expected that pigs reared under commercial conditions have a high probability of developing respiratory compromise before slaughter (Rampelotto et al, 2022).…”
Section: Prevalence Of Antemortem and Postmortem Indicatorsmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], it was noted that the Given and Family names of Karl Ciuoderis-Aponte, Andres Diaz, Carlos Muskus, Juan Hernández-Ortiz and Jorge Osorio were transposed. Furthermore, affiliation 2 incorrectly listed the city and country as Hendersonville, North Carolina, USA.…”
mentioning
confidence: 99%
“…It should be Querato, Mexico. The correct authorship panel and affiliation is shown in this Correction article and the original article [ 1 ] has been updated.…”
mentioning
confidence: 99%